Karakter Giffen Pada Komoditas Arang Tempurung Kelapa - Pitri Yandri (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2017)
The problem of rising fossil energy faced with the limited availability of the commodity in the future. Therefore, it needs new energy sources to tackle the issue. An alternative that can help the economy is the utilization of waste coconut shell that is processed into charcoal. With using principal component analysis, the result of the estimation indicates, there is a unique character that is contained in the shell charcoal commodity. The character of shell charcoal is closed to Giffen goods behavior. The most logical answer is because charcoal is the main raw material of shell burning for a restaurant that has a menu that was burned; and it becomes the unique preferences of the restaurant. They prefer barbecuing their food menu by using charcoal rather than other fuels such as stove, which uses kerosene and LPG. It is because barbecuing with charcoal will produce a better aroma than using the stove with fuel kerosene or LPG.